Pengaruh Gaya Hidup Utilitarian dan Kelompok Acuan terhadap Minat Mengikuti Pembelajaran Online (Studi terhadap BMI Hongkong dalam Mengikuti Pembelajaran Online di Universitas Ciputra) - Kristantoko, Agitya; Iriani, Sri Setyo (BISMA (Bisnis dan Manajemen), 2018)
Increasing of BMI (Indonesian Migrant Workers) who work abroad to provide for his family. But this time the awareness of them increase because becomes migrant worker also increase social cost. Migrant workers Universitas Ciputra This research is conclusive research. Sampling techniques in this study using purposive sampling technique that is 375 BMI are included in an online learning community at the University of Ciputra (potential consumers). Data analysis techniques that used are validity test, reliability test and multiple linear regression analysis with PASW Statistic 1.8 softwareThis study shows the results, that there is a positive effect between utilitarian lifestyle and reference group on purchasing intention online learning in Universitas Ciputra simultaneously and the dominant effect is the utilitarian lifestyle variables followed by variable reference group of online learning community